An Analysis of Uric Acid Level Differencebefore and After Chayote Biscuit Treatment (Sechium Module) on Rats (Rattus Norvegicus) - Rahcmida Rahcmida; Abd. Hakim Leanggeng; Moh. Ansar (Universitas Muhammadiyah Palu, 2021)
Chayote (Sechium module) is a type of vegetable that can be used for various types of food. It is not native to Indonesia but comes from Thailand. It has a fairly complete nutritional content and is also low in purine content. Besides it can be processed as a vegetable, it can also be processed as biscuits. The results of the laboratory test analysis of the content: uric acid level on rats average before intervention (3.84 mg/dL), and mean uric acid level in the day the 8 of intervention (3.26 mg / dL). Differences in treatment levels: before and after the 8th day (p-value = 0.110). This research was conducted at the Laboratory of the Faculty of Mathematics and Natural Sciences, University of Tadulako. This type of research is a laboratory experimental research using paired t-test statistical tests based on the analysis of uric acid levels in rats (Rattus norvegicus) in 2 interventions (treatments). It is expected that the public will make more use of the chayote (Sechium edule) because there are many nutritional contents in chayote which are very beneficial for the health of the body, especially for gout sufferers.